Family, kinship, and sympathy in nineteenth-century American literature - Weinstein, Cindy (Cambridge studies in American literature and culture ;, 2004)
In Family, Kinship, and Sympathy in Nineteenth-Century American Literature Cindy Weinstein radically revises our understanding of nineteenth-century sentimental literature in the United States. She argues that these novels are far more complex than critics have suggested. Rather than confirming the power of the bourgeois family, Weinstein argues, sentimental fiction used the destruction of the biological family as an opportunity to reconfigure the family in terms of love rather than consanguinity. Their texts intervened in debates about slavery, domestic reform and other social issues of the time. Weinstein shows how canonical texts, such as Melville's Pierre and works by Stowe and Twain, can take on new meaning when read in the context of nineteenth-century sentimental fiction. Through intensive close readings of a wide range of novels, this groundbreaking study demonstrates the aesthetic and political complexities in this important and influential genre.